PENGEMBANGAN SISTEM INFORMASI OUTBOUND ORGANIZER PADA PT DUA BERUANG - Togiyana Laurens Purba; Humdiana Humdiana (Jurnal Informatika dan Bisnis, 2015)
In this era of globalization, information and communication technologies have a role in developing the company's business; no exception to the event organizer. In addition to assisting the customer in performing the desired activity, can also help in human resource constraints and the time customers. Outbound organizer application is developed by using programming language based Visual Basic.Net. On the other hand, database is using a MySQL with a connection to the database server using XAMPP. Â This research was conducted by using literature, interviews, and direct observation to PT Dua Beruang. The owner describe all the problems and needs of the author. While the development of the system used was the SDLC (System Development Life Cycle). The findings of this research state are generating an outbound application organizer that can help companies in managing business processes, managing master data information, the data collection activities of resource allocation outbound, outbound packet ordering, and reports that help management companies in making tactical and strategic decisions. The conclusion of this research is the application of information systems developed outbound organizer can provide the simplicity in managing business processes and outbound activities.